The mechanism of ultrasonic irradiation effect on viscosity variations of heavy crude oil - Jinbiao Gao (Elsevier, 2021)
Viscosity reduction of heavy oil has economic benefits and applicational value in the field. Applying viscosity reduction technology of heavy oil with ultrasound, this paper examines the influence of ultrasonic irradiation time and the addition of tetralin and ethylene glycol on viscosity reduction of heavy oil. Fourier Transform Infrared Spectrometer (FTIR) and Gas Chromatograph (GC) were used to analyze the chemical compositions and structural changes of oil samples before and after ultrasonic irradiation, and the effects of ultrasound on viscosity changes are presented. The viscosity reduction rate (VRR) was best at an irradiation time of 6 mins under the current experimental conditions, with VRR reaching more than 80%. When the irradiation time reached 12 mins, the viscosity of oil samples increased conversely. Chemical analysis reveals that the light components in the oil samples increased after the ultrasonic irradiation, indicating that the cavitation, thermal, and mechanical effects of ultrasound could play a role in breaking long chains of carbon, thus reducing the viscosity. The increase in viscosity may have been caused by a reassociation between molecules and/or the coking of heavy oil.